Uniqueness of Two Transcendental Meromorphic Functions Whose Differential Polynomials Share the Value 1 (Journal of Informatics and Mathematical Sciences, 2025)
In 2008, Tao and Wang [3] proved a uniqueness theorem of meromorphic functions whose some nonlinear differential shares 1 IM with powers of the meromorphic functions. In this paper, we improve their results by introducing another transcendental meromorphic function. We prove uniqueness theorem of differential polynomials of two transcendental meromorphic functions whose some nonlinear differential shares 1 IM with powers of the meromorphic functions, where the degrees of the powers are equal to those of the nonlinear differential polynomials.